Worry, Perceived Threat and Media Communication as Predictors of Self-Protective Behaviors During the COVID-19 Outbreak in Europe - Vacondio, Martina; Priolo, Giulia; Dickert, Stephan; Bonini, Nicolao (Frontiers in Psychology, 2021)
Efforts to contain the spread of the coronavirus emphasize the central role of citizens' compliance with self-protective behaviors. Understanding the processes underlying the decision to self-protect is, therefore, essential for effective risk communication during the COVID-19 pandemic. In the present study, we investigate the determinants of perceived threat and engagement in self-protective measures in the UK, Italy, and Austria during the first wave of the pandemic. The type of disease (coronavirus versus seasonal flu) and the type of numerical information regarding the disease (number of recovered versus number of dead) were manipulated. Participants' cognitive and emotional risk assessment as well as self-reported engagement in protective behaviors were measured. Results show that worry was the best predictor of perceived threat in all countries. Moreover, a path analysis revealed that worry and perceived threat serially mediated the effect of type of disease on engagement in self-protective behaviors. The framing manipulation did not significantly impact behavior but had a direct effect on worry and an indirect effect on perceived threat. These results are in line with theoretical accounts that identify emotions as a central determinant for risk perception. Moreover, our findings also suggest that effective risk communication during the COVID-19 pandemic should not stress comparisons to other viral diseases, as this can ultimately reduce self-protective behaviors.